Fényképek gyermekeinknek - Kőszegi, Edit; Simó, Sándor; Surányi, András (Hungary, 1988)
Holocaust survivors, Jews from Budapest, tell their personal stories about their experiences during World War 2. With the help of family and official photographs, documents and newsreels, elderly Jews talk about the anti-Jewish laws, forced labour service, confiscation of property, having to wear the yellow star, ghettoization, life in yellow-star houses and the ghetto, the Arrow Cross murder of Jews, and finally, the Liberation. Budapesti zsidók második világháborús üldöztetésének kordokumentuma a film: túlélők mesélik el személyes történeteiket családi fotók, tábori levelek, dokumentumok segítségével. A filmben idős emberek emlékeznek vissza arra, hogy milyen volt a munkaszolgálat 1941-től, a sárga csillag viselése, a csillagos házakba való kényszerű beköltözés 1944. nyarán, a nyilas hatalomátvétel, öldöklés, a gettó és a felszabadulás.
Duration: 01:15:00
Yellow Star Houses Film Program 2014
Keywords: Documentary films